Nudge Theory in Action : A Strategic Approach to Strengthening Cybersecurity in Organizations. - Kuznetsov, Mikhail; Ali, Tanweer; Kupec, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The purpose of this bachelor’s thesis is to explore the usage and of nudge theory as a means to address the growing cyber threats. The theoretical part establishes the basis for understanding of nudge theory and its applications, in particular in the field of cybersecurity. Then in the practical part it provides an analysis of interviews conducted with people whose work relates to cybersecurity and one with a nudge researcher done using the reflexive thematic analysis approach. During the interviews the respondents provided insights into the current state of nudging implementation, benefits, limitations and risks associated with nudges, addressed the criticism of the nudge theory and gave their forecasts about the future of nudges in cybersecurity. The thesis gives a detailed overview of the interviews, formulates practical recommendations stemming from the results of the interviews and establishes the areas for potential future research on this topic.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses